The Relationship of Self-confidence with Dribbling Skill: A Correlation Study on Young Football Players - Razali Razali; Zulfikar Zulfikar; Karimuddin Karimuddin; Myra Akbari (Proceedings of AICS - Social Sciences, 2021)
Dribbling is one type of skill that must be possessed by a football player. One indicator of the quality of a good football player is being able to show good dribbling skills when playing football. Based on theoretical studies, to be able to dribble well, a football player must have a good mentality; one of the mentalities needed when dribbling is to have good self-confidence. The purpose of this study was to determine the relationship between variables, namely self-confidence and dribbling skills. This research approach is quantitative with the type of correlational research. The population in this study was young players from the "Talenta Aceh" football academy, totaling 36 players. The measurement instruments used for the two variables are (1) the self-confidence instrument using a questionnaire developed by the author and (2) dribbling using the "Dribbling Test". The analysis of research data used the product-moment correlation formula which aimed to determine the correlation coefficient between the two variables. Based on the results of data analysis, it can be concluded that there is a significant relationship between self-confidence and dribbling skills, with a correlation coefficient value (r = 0.56); based on the value of the correlation coefficient, self-confidence contributes 42.25% to dribbling skills.Keywords: Young player, football, self-confidence, dribbling.